1974
DOI: 10.1128/jb.118.2.534-540.1974
|View full text |Cite
|
Sign up to set email alerts
|

Porosity of the Yeast Cell Wall and Membrane

Abstract: The limiting sizes of molecules that can permeate the intact cell wall and protoplast membrane of Saccharomyces cerevisiae were determined from the inflection points in a triphasic pattern of passive equilibrium uptake values obtained with a series of inert probing molecules varying in molecular size. In the phase identified with the yeast protoplast, the uptake-exclusion threshold corresponded to a monodisperse ethylene glycol of molecular weight = 110 and Einstein-Stokes hydrodynamic radius (rEs) = 0.42 nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(68 citation statements)
references
References 17 publications
3
64
0
1
Order By: Relevance
“…The elasticity of the wall explains why the wall of living cells is much more permeable than isolated cell walls. Whereas isolated walls are permeable only to molecules of molecular mass up to 760 Da [30], walls of living cells are permeable to much larger molecules especially under hypotonic conditions and also depending on growth conditions [22,31,32].…”
Section: Composition and Properties Of The Cell Wallmentioning
confidence: 99%
“…The elasticity of the wall explains why the wall of living cells is much more permeable than isolated cell walls. Whereas isolated walls are permeable only to molecules of molecular mass up to 760 Da [30], walls of living cells are permeable to much larger molecules especially under hypotonic conditions and also depending on growth conditions [22,31,32].…”
Section: Composition and Properties Of The Cell Wallmentioning
confidence: 99%
“…The measurement of the equilibrium distribution coefficient (k = Cin/Cout) of ethanol between the cytoplasm and the extracellular broth requires a distinction to be drawn between whole cell and cytoplasmic measurements. In the case of whole cell distribution coefficients the water space occupied by the cell wall plus the periplasrnic space accounts for some 15 to 25% of the total cellular water [34,42,[74][75][76]. The equilibrium distribution coefficient of solutes into this water appears to be higher than that of the cytoplasmic water [75,76], mainly due to the contribution of the periplasmic space, and so whole cell coefficients are typically higher than the true cytoplasmic value.…”
Section: Distribution Into Cell Watermentioning
confidence: 99%
“…In the case of whole cell distribution coefficients the water space occupied by the cell wall plus the periplasrnic space accounts for some 15 to 25% of the total cellular water [34,42,[74][75][76]. The equilibrium distribution coefficient of solutes into this water appears to be higher than that of the cytoplasmic water [75,76], mainly due to the contribution of the periplasmic space, and so whole cell coefficients are typically higher than the true cytoplasmic value. For whole yeast cells values of the distribution coefficient of around 0.95 are common [36,38].…”
Section: Distribution Into Cell Watermentioning
confidence: 99%
“…However, the yeast estrogen bioassay showed the best correlation with the uterotrophic assay (R 2 = 0.87). Although yeast cell-based assays are thought to suffer from poor transport of chemicals across the yeast cell wall, previous studies demonstrated that the yeast cell wall is easily permeable for compounds with a molecular weight up to 620 or even larger molecules owing to the flexibility of the wall of living yeast cells (De Nobel and Barnett, 1991;Scherrer et al, 1974). Thus, the yeast cell wall does not provide a major obstacle for low-molecular-weight compounds to reach the inside of the cells and activate the ER.…”
Section: Discussionmentioning
confidence: 99%